UV radiation induces CXCL5 expression in human skin - Reichert, Olga; Schmelz, Martin (Experimental dermatology, 2015)
CXCL5 has recently been identified as a mediator of UVB-induced pain in rodents. To compare and to extend previous knowledge of cutaneous CXCL5 regulation, we performed a comprehensive study on the effects of UV radiation on CXCL5 regulation in human skin. Our results show a dose-dependent increase in CXCL5 protein in human skin after UV radiation. CXCL5 can be released by different cell types in the skin. We presumed that, in addition to immune cells, non-immune skin cells also contribute to UV-induced increase in CXCL5 protein. Analysis of monocultured dermal fibroblasts and keratinocytes revealed that only fibroblasts but not keratinocytes displayed up regulated CXCL5 levels after UV stimulation. Whereas UV treatment of human skin equivalents, induced epidermal CXCL5 mRNA and protein expression. Up regulation of epidermal CXCL5 was independent of keratinocyte differentiation and keratinocyte-keratinocyte interactions in epidermal layers. Our findings provide first evidence on the release of CXCL5 in UV-radiated human skin and the essential role of fibroblast-keratinocyte interaction in the regulation of epidermal CXCL5.